Hybrid Molecules of Azithromycin with Chloramphenicol and Metronidazole: Synthesis and Study of Antibacterial Properties - Inna A. Volynkina; Elena N. Bychkova; Anastasiia O. Karakchieva; Alexander S. Tikhomirov; George V. Zatonsky; Svetlana E. Solovieva; Maksim M. Martynov; Natalia E. Grammatikova; Andrey G. Tereshchenkov; Alena Paleskava; Andrey L. Konevega; Petr V. Sergiev; et al. (MDPI AG, 2024)
The sustained rise of antimicrobial resistance (AMR) causes a strong need to develop new antibacterial agents. One of the methods for addressing the problem of antibiotic resistance is through the design of hybrid antibiotics. In this work, we proposed a synthetic route for the conjugation of an azithromycin derivative with chloramphenicol and metronidazole hemisuccinates and synthesized two series of new hybrid molecules 4a-g and 5a-g. While a conjugation did not result in tangible synergy for wild-type bacterial strains, new compounds were able to overcome AMR associated with the inducible expression of the ermC gene on a model E. coli strain resistant to macrolide antibiotics. The newly developed hybrids demonstrated a tendency to induce premature ribosome stalling, which might be crucial since they will not induce a macrolide-resistant phenotype in a number of pathogenic bacterial strains. In summary, the designed structures are considered as a promising direction for the further development of hybrid molecules that can effectively circumvent AMR mechanisms to macrolide antibiotics.